Simultaneous Ablation of Uterine Natural Killer Cells and Uterine Mast Cells in Mice Leads to Poor Vascularization and Abnormal Doppler Measurements That Compromise Fetal Well-being - Meyer, Nicole; Schüler, Thomas; Zenclussen, Ana Claudia (Frontiers in Immunology, 2018)
Intrauterine growth restriction (IUGR) is a serious pregnancy complication with short- and long-term health consequences. The mechanisms underlying this condition are not well understood. Animal models are the basis for understanding the causes of IUGR and for developing useful therapeutic strategies. Here, we aimed to ascertain the in utero growth of fetuses from NK/MC-deficient mothers that give birth to growth restricted pups and to determine the time point at which IUGR starts. We used high frequency ultrasound imaging to follow up fetal and placenta size and employed Doppler measurements to document blood supply to the fetus in females that were deficient for NK cells and MCs. In mice lacking NKs and MCs we observed significantly reduced implantation sizes from mid gestation onwards, which was further associated with smaller placentas. Additionally, NK/MC-deficiency was associated with absent and reversed end diastolic flow in umbilical arteries of the fetuses and an increased systolic/diastolic ratio as well as an elevated resistance index. Together, our results indicate that NKs/MCs promote blood flow, placental growth and subsequent fetal development. The results of this study offer new insights as to how fetal growth is affected in vivo in NK/MC-deficient mice, whose pups are growth restricted at birth. The use of IUGR models and modern technologies enabling the in vivo follow-up of fetal development are important tools for understanding mechanisms behind pregnancy complications that in the future may lead to the development of effective therapies.